Analisis kes-kes khuluk di Mahkamah Rendah Syariah Wilayah Persekutuan Kuala Lumpur - Daud Mohd Noor, Ismail Abdul Munir, Abd Ghani Abdul Rahman, Kasim Ahmad Yunus (Universiti Pendidikan Sultan Idris, 2016)
Analisis kes-kes khuluk di Mahkamah Rendah Syariah Wilayah Persekutuan Kuala Lumpur by Daud Mohd Noor, Ismail Abdul Munir, Abd Ghani Abdul Rahman, Kasim Ahmad Yunus,